7-hydroxyfrullanolide, isolated from Sphaeranthus indicus, inhibits colorectal cancer cell growth by p53-dependent and -independent mechanism. (8th December 2018) - Pandey, Praveen; Singh, Deepika; Hasanain, Mohammad; Ashraf, Raghib; Maheshwari, Mayank; Choyal, Kuldeep; Singh, Akhilesh; Datta, Dipak; Kumar, Brijesh; Sarkar, Jayanta
Abstract: Sphaeranthus indicus Linn. is commonly used in Indian traditional medicine for management of multiple pathological conditions. However, there are limited studies on anticancer activity of this plant and its underlying molecular mechanisms. Here, we isolated an active constituent, 7-hydroxyfrullanolide (7-HF), from the flowers of this plant, which showed promising chemotherapeutic potential. The compound was more effective in inhibiting in vitro proliferation of colon cancers cells through G2 /M phase arrest than other cancer cell lines that were used in this study. Consistent with in vitro data, 7-HF caused substantial regression of tumour volume in a syngeneic mouse model of colon cancer. The molecule triggered extrinsic apoptotic pathway, which was evident as upregulation of DR4 and DR5 expression as well as induction of their downstream effector molecules (FADD, Caspase-8). Concurrent activation of intrinsic pathway was demonstrated with loss of ΔΨm to release pro-apoptotic cytochrome c from mitochondria and activation of downstream caspase cascades (Caspase -9, -3). Loss of p53 resulted in decreased sensitivity of cells towards pro-apoptotic effect of 7-HF with increased number of viable cells indicating p53-dependent arrest of cancer cell growth. This notion was further supported with 7-HF-mediated elevation of endogenous p53 level, decreased expression of MDM2 and transcriptional upregulation of p53 target genes in apoptotic pathway. However, 7-HF was equally effective in preventing progression of HCT116 p53 +/+ and p53 −/− cell derived xenografts in nude mice, which suggests that differences in p53 status may not influence its in vivo efficacy. Taken together, our results support 7-HF as a potential chemotherapeutic agent and provided a new mechanistic insight into its anticancer activity.